THERAPEUTIC APPROACHES TO MEDULLOBLASTOMA - Martins, Arnaldo Barbosa; de Castilho, Pedro Augusto Godinho; do Nascimento, Ana Paula Veloso; Góis, Lucas Jaffé de Carvalho; Leite, Genesis Ribeiro; Goulart, Danielle Magalhães Sá; Santos, Rubia Martinez; Linhares, Roseane Barros (Seven Editora, 2026)
Medulloblastoma is the most prevalent malignant brain neoplasm in the pediatric population, characterized by marked clinical and biological heterogeneity and stratified into four main molecular subgroups: WNT, SHH, Group 3, and Group 4. Although traditional management with surgical resection, craniospinal radiotherapy, and chemotherapy has improved cure rates, survivors frequently develop severe neurocognitive and endocrine deficits due to the toxicity of conventional treatment. This narrative literature review, based on PubMed articles published between 2021 and 2025, sought to synthesize advances in therapeutic approaches to medulloblastoma. The results highlight the emergence of targeted therapies, such as DHODH enzyme inhibition for Group 3 medulloblastoma (frequently associated with MYC oncogene amplification) and the identification of new cell survival mechanisms. In monitoring, cerebrospinal fluid (CSF) liquid biopsy has become established for the assessment of measurable residual disease (MRD). Furthermore, new immunotherapy strategies focused on NK cells and checkpoint blockade are being explored to overcome immune evasion. It is concluded that the future of medulloblastoma management lies in combining dynamic monitoring via liquid biopsy with polytherapies that simultaneously target oncogenic signaling and aberrant cellular metabolism, seeking to balance tumor control with the preservation of neurological functions and child development.